Practical application of a novel prefabricated curling ice rink supported by steel–concrete composite floors: In situ measurements of static and dynamic response. (August 2021) - Zhang, Wenyuan; Li, Junxing; Yang, Qiyong; Mu, Liang
Abstract: On the basis of not destroying the original function, the non-curling field is transformed into a new curling ice rink that meets certain professional requirements through the detachable and prefabricated structure. This curling ice rink is an innovative type of prefabricated curling rink compared with the traditional rink, which has excellent advantages in terms of functional transformation and refrigerating efficiency. However, due to the vibration of the supporting structure and the deformation of the insulation foam under the ice layer, the annoying vibration and ice surface cracking are easy to occur. The static and dynamic performance of the new type of prefabricated curling ice rink located in Beijing, China, in the National Aquatics Center (Water Cube) was analyzed by a series of in situ tests. The field test consisted of two phases: the steel-framed concrete slab prefabricated structure test before ice making and the curling ice rink test after ice making. Phase 1 consisted of graded static load test and dynamic characteristic test as well as analytical frequency predictions. Phase 2 included static load test and dynamic test, long-term vertical deformation at the center point of column grid region on the precast concrete slabs for 19 days, and horizontal deformation at key points of the curling rink during 2019 China Junior Curling Open. A 3D finite element model was established using ABAQUS software, and the natural frequency and key deformation values obtained by modeling were compared with the corresponding ones from experiments. According to the proposed evaluation criteria, the results show that the mechanical properties and deformation ability of this new type of functional transformation curling rink are suitable for application in large international competitions.